Екологічний аспект просторової неоднорідності едафотопів техногенного походження - Задорожна, Галина; Zadorozhna, Galina (Східноєвропейський національний університет імені Лесі Українки, 2016)
Досліджено динаміку просторової неоднорідності педозему ділянки рекультивації Нікопольського мар-ганцеворудного басейну в м Орджонікідзе за показниками твердості. Проведено екоморфічний аналіз рослин-ності ділянки. Методом неметричного багатовимірного шкалювання здійснено ординацію даних твердості ґрунту. Застосовано тривимірний варіант багатовимірного шкалювання. Виділено характерні для вивченого ґрунту типи розподілу твердості за профілем. Взаємозв’язок варіювання твердості ґрунту й факторів навколишнього середовища встановлено при використанні фітоіндікаційних шкал. За допомогою техніки просторового аналізу даних (PCNM) виділено просторові структури на різних масштабних рівнях і визначено процеси, що лежать у їх основі. The dynamics of spatial heterogeneity of the pedozem site reclamation of the Nikopol manganese ore basin in Ordzhonikidze has been studied in terms of hardness. The ecomorphic analysis of vegetation of the section has been spent. The ordination of data of soil hardness has been realized by non-metric multidimensional scaling. The three-dimensional variant of multidimensional scaling has been applied. The types of distribution of hardness in the profile typical of studied soil have been distinguished. The relationship of varying the hardness of the soil and environmental factors has been set using phytoindicative scales. For receipt most rank correlation has been used matrix based on distance the Chao with indicators pre-standardized to the range 0-1. It was established that factors forming the first coordination axis of environmental space is change the hardness of the soil, depending on the depth of the soil layer. There is interconnected opposite dynamics of soil hardness in layers of 30 cm below the profile with indicators of layers lying above the selected block. The scales of hydromorph, solt regime, such a structure of the soil, when there are there are significant differences in the hardness of the soil above and below the level of 25 cm from the surface with the most significant values of the hardness of the surface layer determine the second dimension. The highest value in the formation of the third dimension by the predictor has scale of light. In the latter case, the hardness of the soil at 10–35 cm depth profile will be different from surrounding. Using the technique of spatial data analysis (PCNM) has been highlighted the spatial structure at different scale levels and defined processes their underlying. It was established the trophic of soil is important for the formation of large-scale components of soil heterogeneity. The inhomogeneities of detailed scale mark by salt soil regime, its acidity, content of digestible nitrogen forms, mode lighting and presence in the group of plant different gigromorfes.
Environmental Aspect of Spatially Inhomogeneous of Technogenic Origin Edafotops
Keywords: твердість ґрунту; багатовимірне шкалювання; педозем; екоморфічний аналіз; soil hardness; multidimensional scaling; pedozems; ecomorphic analisis